Pengaruh Tingkat Pendidikan Formal Terhadap Kompetensi Mengajar Guru Sekolah Minggu - Dessy Ari Wardhani; Andrias Pujiono (Institut Agama Kristen Negeri Kupang, 2022)
The level of education of Sunday school teachers is one of the important factors for Sunday school teaching competence. As a Sunday school teacher who is professional in his field, he is expected to have good teaching competence as well. To determine the effect of education level on the teaching competence of Sunday school teachers at the Bethel Tabernacle Church (GBT) in Lampung Province, a study was conducted regarding this matter. The purpose of this study was to see whether there was an effect of teacher education level on their competence. If the level of education is low, the teaching competence is low, and vice versa. With a quantitative approach, data collection techniques through questionnaires with a Likert scale, and data processing using SPSS obtained a correlation number of 0.308. Based on the correlation coefficient table, this figure is included in the low category. That is, there is a low correlation between Education Level (X) and Teaching Competence (Y). Meanwhile, to see how much the X variable contributes to Y, the determinant coefficient test is carried out and gets a figure of 9.5%.